HUBUNGAN KEMATANGAN EMOSI DENGAN PERENCANAAN KARIR SISWA KELAS X SMK MA’ARIF NU TONJONG BREBES: HUBUNGAN KEMATANGAN EMOSI DENGAN PERENCANAAN KARIR SISWA - Anang Pratama, Rifqy (Prodi Bimbingan dan Konseling universitas PGRI Semarang, 2025)
The background that motivates this research is the lack of emotional maturity among students regarding decision-making, which is related to career planning. The aim of this study is to determine whether there is a relationship between emotional maturity and career planning among 10th-grade students at SMK Ma’arif NU Tonjong Brebes. This type of research is correlational. The population in this study includes all 10th-grade students at SMK Ma’arif NU Tonjong Brebes. From the existing population, a sample was taken using purposive sampling technique, totaling 86 students from three classes. The analysis technique used is Product Moment correlation. The results of the study indicate that 1) Career planning among 10th-grade students at SMK Ma’arif NU Tonjong Brebes falls into the low category for 40 students, representing 46%. 2) Emotional maturity among 10th-grade students at SMK Ma’arif NU Tonjong Brebes falls into the moderate category for 34 students, representing 40%. The results show a significant relationship between the two variables with a correlation value of 0.554. Based on the research findings, it is recommended that the school optimize existing programs in counseling services (BK) by providing supporting facilities so that counseling teachers or counselors and subject teachers can offer maximum service programs.